A High-Feasibility Secure Routing against Malicious Peer in Structured P2P. (28th September 2022) - Wang, Feng; Xuan, Chunqing
Abstract : As applications based on the structured peer-to-peer network have increased, the importance of security is increasing. Routing is the core of the structured peer-to-peer network, naturally which becomes the primary target of malicious nodes. The current attacks on the routing by malicious nodes are mainly sybil attacks, eclipse attacks, and routing table poisoning. In previous studies of defending above attacks, either adding redundancy to achieve security or sacrificing network scalability for security. So we establish a mathematical model of the routing process, and through the model, we analyze sybil attacks, eclipse attacks, and routing table poisoning. The same essence is found that these attacks all undermine the original convergence of the query path, and with the convergence detection, we propose the security mechanism HFS-Routing, and we design experiments and analyze the results. The results show that HFS-Routing has a lower overhead, better scalability, and higher detection rates for the malicious nodes, which is a highly feasibility mechanism.